Determinant roles of gender and age on SII, PLR, NLR, LMR and MLR and their reference intervals defining in Henan, China: A posteriori and big‐data‐based. Issue 2 (5th April 2017) - Meng, Xianchun; Chang, Qian; Liu, Yuying; Chen, Ling; Wei, Gaohui; Yang, Jingjing; Zheng, Peiguo; He, Fucheng; Wang, Wanhai; Ming, Liang
Abstract : Objectives: By now, there are few data of the reference intervals (RIs) of SII, PLR, NLR, LMR and MLR. We aimed to establish RIs of SII, PLR, NLR, LMR and MLR for healthy persons. Methods: A retrospective analysis on a cohort of ostensibly healthy, aged no <18 years old physical examinees who took health examination from January to December in 2013 was conducted to explore influences of age and gender on SII, PLR, NLR, LMR and MLR and to establish their RIs. And another cohort of 450 persons in our hospital from January to July in 2016 is included for validations of RIs. Results: NLR, LMR and MLR were significantly different between gender groups ( P =.010; P <.001; P <.001, separately), while SII and PLR were not ( P =.137; P =.267, separately). While SII was not changed much between age groups ( P =.842), PLR, NLR, LMR and MLR were significantly different (all with P <.001). RIs of SII, PLR, NLR, LMR and MLR were: SII: [161, 701]; PLR: 18‐65 year‐old: [61, 179]/>65 year‐old: [55, 179]; NLR: 18‐65 year‐old male: [0.90, 2.94]/18‐65 year‐old female: [0.85, 3.06]/>65 year‐old male: [0.95, 3.57]/aged >65 year‐old female: [0.83, 3.30]; LMR: 18‐65 year‐old male: [2.50, 7.50]/18‐65 year‐old female: [2.75, 8.50]/>65 year‐old male: [2.16, 7.41]/>65 year‐old female: [2.40, 8.33]; MLR: 18‐65 year‐old male: [0.12, 0.35]/18‐65 year‐old female: [0.10, 0.32]/>65 year‐old male: [0.12, 0.41]/>65 year‐old male: [0.11, 0.33]. Conclusions: RIs of SII, PLR, NLR, LMR and MLR of people in central China were established and validated. It will benefit experimental design of the related studies and lead to better standardizations of SII, PLR, NLR, LMR and MLR for their clinical applications.